HDL mimetic CER-001 targets atherosclerotic plaques in patients. (August 2016) - Zheng, Kang He; van der Valk, Fleur M.; Smits, Loek P.; Sandberg, Mara; Dasseux, Jean-Louis; Baron, Rudi; Barbaras, Ronald; Keyserling, Constance; Coolen, Bram F.; Nederveen, Aart J.; Verberne, Hein J.; Nell, Thijs E.; et al.
Abstract: Background and aims: Infusion of high-density lipoprotein (HDL) mimetics aimed at reducing atherosclerotic burden has led to equivocal results, which may relate in part to the inability of HDL mimetics to adequately reach atherosclerotic lesions in humans. This study evaluated delivery of recombinant human apolipoprotein A-I (apoA-I) containing HDL mimetic CER-001 in carotid plaques in patients. Methods: CER-001 was radiolabeled with the long-lived positron emitter zirconium-89 ( 89 Zr) to enable positron emission tomography with computed tomography (PET/CT) imaging. Eight patients with atherosclerotic carotid artery disease (>50% stenosis) received a single infusion of unlabeled CER-001 (3 mg/kg), co-administered with 10 mg of 89 Zr-labeled CER-001 (18 MBq). Serial PET/CT imaging and contrast enhanced-magnetic resonance imaging (CE-MRI) were performed to evaluate targeted delivery of CER-001. Results: One hour after infusion, mean plasma apoA-I levels increased by 9.9 mg/dL ( p  = 0.026), with a concomitant relative increase in the plasma cholesterol efflux capacity of 13.8% ( p  < 0.001). Using serial PET/CT imaging, we showed that arterial uptake of CER-001 expressed as target-to-background ratio (TBRmax ) increased significantly 24 h after infusion, and remained increased up to 48 h (TBRmax t = 10 min: 0.98; t = 24 h: 1.14 ( p  = 0.001); t = 48 h: 1.12 ( p  = 0.007)). TBRmax was higher in plaque compared with non-plaque segments (1.18 vs . 1.05; p  < 0.001). Plaque TBRmax correlated with local plaque contrast enhancement (r = 0.56; p  = 0.019) as assessed by CE-MRI. Conclusions: Infusion of HDL mimetic CER-001 increases plasma apoA-I concentration and plasma cholesterol efflux capacity. Our data support the concept that CER-001 targets plaque regions in patients, which correlates with plaque contrast enhancement. These clinical findings may also guide future nanomedicine development using HDL particles for drug delivery in atherosclerosis. Clinical trial registration: Netherlands Trial Registry – NTR5178. http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=5178 . Graphical abstract: Highlights: HDL infusion therapies for atherosclerosis have so far been equivocal. HDL mimetic CER-001 was radiolabeled with 89 Zr to allow for clinical PET/CT imaging. 89 Zr-labeled CER-001 PET signal was higher in plaques than in non-plaque segments. Plaque uptake of 89 Zr-labeled CER-001 correlated with local contrast enhancement. These findings may support future nanomedicine development using HDL particles.